Rancang Bangun Mesin Pemotong Kentang Stick dengan Sistem Pemasak dan Pemberian Rasa Otomatis Berbasis IoT - Cendrakasih, Aminah; Salamah, Irma; Rakhman, Abdul Halim (Program Studi Teknik Informatika Universitas Pamulang, 2024)
Potatoes are one of the most popular snacks, especially in the food industry, where they are often processed into potato sticks. However, the production process for ready-to-eat potato sticks tends to be complex and requires significant time and labor. This research designs a potato stick cutting machine with an automatic cooking and seasoning system using Internet of Things (IoT) technology to simplify the production process. The machine is integrated with an IoT network and equipped with an Android application for system monitoring. Microcontrollers act as the main controller, managing machine operations based on instructions from the Android application and sensors on the machine. The result of this research is the development of an intelligent machine that can produce potato sticks with guaranteed quality and consistency according to user preferences. This machine also improves production efficiency by reducing the time and labor required, and it provides ease of monitoring and controlling the production process remotely through the Android application, thereby significantly contributing to the modern food industry.